UPAYA MENURUNKAN POPULASI HAMA PADA BUDIDAYA SISTEM TUMPANG SARI DI LAHAN PASIR PANTAI = REDUCING PEST POPULATION IN MULTIPLE CROPPING SYSTEM ON SANDY COASTAL LAND - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Sandy coastal land is marginal land with promising potential if suitable culture technique was practiced therein. Farmers apply multiple cropping system in utilizing these lands, especially those located in the southern coast of Yogyakarta, viz. Bantul and Kulon Progo regencies. The multiple cropping system successfully address the need of optimizing the land, but in term of synthetic chemical inputs such as fertilizer and pesticides, the farmers still rely heavily on them, which may endanger the system and threaten the environment. Multiple cropping system in itself actually promotes organism's biodiversity, therefore chemical inputs should be used with extra care. This study tries to find out whether multiple cropping system in sandy coastal land has the ability to suppress pests population because of its biodiversity, which will in turn reduce chemical inputs. The study was done in Bantul regency for one planting season, using corn, shallot, chilli pepper and choy-sim in a multiple cropping system, which was subjected to pesticides and no pesticides application. Plant growth, pest population and LER (Land Equivalent ratio) were then determined. The result showed that the multiple cropping system without pesticides produce better than the one with pesticides, as shown by the observed pest population dynamics and the calculated LER values.